Determinants of Financial Behaviours among Malaysians - Ahmad, Zauwiyah; Simun, Maimun; Masuod, Md. Shukor (The Indonesian Capital Market Review, 2010)
The importance of financial literacy in promoting good financial behaviour has been established in previous studies. Nonetheless, a study that speciically analyses Malaysian or Asian general public is very rare, despite various cases involving bankruptcies, suicides and harassment that result from improper financial decisions within the region. This study focuses on Malaysians' financial literacy and inancial behaviour. It is hypothesized that inancial behaviour is signiicantly correlated with financial literacy. It is also expected that Malaysians' inancial behaviour and financial literacy vary signiicantly among those from different education and income levels. A quantitative approach was adopted for this study, utilizing questionnaire survey as the main research instrument. Results showed signiicant, positive correlation between financial literacy and financial behaviour. Moreover, less educated individuals and lower income earners were found to have lower financial literacy. This paper provides a discussion on educational programmes that could be conducted in order to enhance the public's financial literacy and promotes good financial practices, especially among these groups of individuals.